2011
DOI: 10.5194/hess-15-3135-2011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of land surface temperature on soil moisture anomaly detection from passive microwave observations

Abstract: Abstract. For several years passive microwave observations have been used to retrieve soil moisture from the Earth's surface. Low frequency observations have the most sensitivity to soil moisture, therefore the current Soil Moisture and Ocean Salinity (SMOS) and future Soil Moisture Active and Passive (SMAP) satellite missions observe the Earth's surface in the L-band frequency. In the past, several satellite sensors such as the Advanced Microwave Scanning Radiometer-EOS (AMSR-E) and WindSat have been used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…Many contributing factors (e.g., soil moisture, superficial profile of soil temperature, and phenology) are required to explain the behavior of the two passive microwave indices in Alice Springs and Sturt Plains. In particular, in these sparse vegetated sites, the observed radiation was not simply produced at the air/soil interface, and FI variations can be explained by variations of temperature profile, in agreement with previous works [Parinussa et al, 2011;Norouzi et al, 2012].…”
Section: Discussionsupporting
confidence: 78%
“…Many contributing factors (e.g., soil moisture, superficial profile of soil temperature, and phenology) are required to explain the behavior of the two passive microwave indices in Alice Springs and Sturt Plains. In particular, in these sparse vegetated sites, the observed radiation was not simply produced at the air/soil interface, and FI variations can be explained by variations of temperature profile, in agreement with previous works [Parinussa et al, 2011;Norouzi et al, 2012].…”
Section: Discussionsupporting
confidence: 78%
“…A consequence is that the existing linear regression is extrapolated outside its calibrated range, resulting in LST errors which manifest themselves in the soil moisture algorithm. A previous study [7] demonstrated this, and showed that refining this LST regression can lead to enhanced soil moisture anomalies with significantly larger improvements possible for the day-time over the night-time observations. In contrast with the degrading impact of T s and T c differences, it was suggested that higher LST observed during the day-time may result in a higher transparency of the vegetation, allowing for better penetration of the soil moisture emission through the canopy.…”
mentioning
confidence: 80%
“…The R value verification technique (Section 3.2.1) is based on the connection between precipitation and the subsequent changes in soil moisture and therefore requires precipitation data as an input [7,16]. The precipitation product that was used here is the Tropical Rainfall Monitoring Mission (TRMM) 3B42 (v7) product.…”
Section: Precipitation Datamentioning
confidence: 99%
“…TCA is a statistical method for characterizing consensus and discrepancies across multiple independent datasets. Though developed originally for oceanographic applications (Stoffelen, 1998), the method has recently been applied successfully to the problem of estimating soil moisture variability at regional to global scale Hain et al, 2011;Parinussa et al, 2011;Yilmaz et al, 2012). TCA is of particular value in regions that lack in situ soil moisture monitoring networks, as consensus anomaly estimates derived from multiple independent datasets can be interpreted as a measure of confidence in the absence of adequate in situ evaluation data.…”
Section: Introductionmentioning
confidence: 99%